The West African dwarf sheep. 1. Reproductive performance and growth - Dettmers, A.; Igoche, C.A.; Akinkuolie, K. (1976)
The reproductive performance and growth rate of West African Dwarf sheep under improved management condition were investigated. Data on productivity, breeding efficiency, weight gain, lambing characteristics and mortality included.